Noticia del hallazgo de un epígrafe altoimperial en el lugar de Pelou, Grandas de Salime (Asturias) - Villa Valdés, Ángel; Francisco Martín, Julián de; Alföldy, Géza (Archivo español de arqueología, 2005)
The present paper reports the discovery at Monte Castrelo de Pelou (Asturias, Spain) of an epigraphic inscription dated at the first Century AD. Monte Castrelo is a little hillfort located in the vicinity of Grandas de Salime township, in the western area of Asturias, in northern Spain. This site was traditionally considered a Roman mining settlement, but current archaeological research unveiled the existence of much older occupation strata underlying the Imperial Roman context where the described inscription was located. The new archaeological data reveal that the site was a fortified settlement already during the Iron Age, being reoccupied, again with a military function, during the fourth century AD. - The inscription is engraved in cursives on a slate panel. It contains a list of probably 45 to 50 names, although just around 35 of them are still legible to some extent. It is tentatively interpreted as an administrative document reflecting the census of population under control of the hillfort's garrison.
Gesehen am 22.03.2024